Epitaxial growth of metallic buffer layer structure and c-axis oriented Pb(Mn1/3, Nb2/3)O3–Pb(Zr, Ti)O3 thin film on Si for high performance piezoelectric micromachined ultrasonic transducer. (21st November 2017) - Thao, Pham Ngoc; Yoshida, Shinya; Tanaka, Shuji
Abstract: This paper reports on the development of a metallic buffer layer structure, (100) SrRuO3 (SRO)/(100) Pt/(100) Ir/(100) yttria-stabilized zirconia (YSZ) layers for the epitaxial growth of a c -axis oriented Pb(Mn1/3, Nb2/3 )O3 –Pb(Zr, Ti)O3 (PMnN–PZT) thin film on a (100) Si wafer for piezoelectric micro-electro mechanical systems (MEMS) application. The stacking layers were epitaxially grown on a Si substrate under the optimal deposition condition. A crack-free PMnN–PZT epitaxial thin films was obtained at a thickness up to at least 1.7 µm, which is enough for MEMS applications. The unimorph MEMS cantilevers based on the PMnN–PZT thin film were fabricated and characterized. As a result, the PMnN–PZT thin film exhibited −10 to −12 C/m 2 as a piezoelectric coefficient e 31, f and ∼250 as a dielectric constants εr . The resultant FOM for piezoelectric micromachined ultrasonic transducer (pMUT) is higher than those of general PZT and AlN thin films. This structure has a potential to provide high-performance pMUTs.